The Mechanism for Driving Ethical Behavior through the 7-Step towards Sufficiency: A Grounded Theory Study - Phanwong, Sumet; Promnarai, Worada; Praditduang, Rattanakraw; Thawinkarn, Dawruwan; Kerdsrithong, Atcharawadee (An Online Journal of Education, 2026)
This research aimed to study the mechanisms for driving ethical behavior through the 7-step towards sufficiency in educational institutions. The study employed a qualitative research methodology based on grounded theory. informants included administrators, teachers, students, school board members, community leaders, and parents with a total of 17 individuals from a school in Udon Thani province which serves as a model school for education management based on the sufficiency economy philosophy. Research instruments consisted of semi-structured interviews, focus group discussion record form, observation and field note recording form, and document review form. Data were analyzed using content analysis based on Strauss and Corbin's (1998) approach in conjunction with analytic induction. The research findings revealed that the mechanisms for driving ethical behavior through the 7-step towards sufficiency included: (1) start with yourself, (2) set clear goals, (3) follow sequential steps, (4) think positively and create happiness, (5) understand others and yourself, (6) collaborate to create new things, and (7) practice to form habits. The mechanisms were categorized into three types: (1) driving mechanisms, which emphasize participatory processes involving individuals, the school, and the wider community; (2) supporting mechanisms, which involve the integration of home, temple, and school, and community-based faith and trust; and (3) embedded mechanisms, which include the support from the responsible supervisory authorities, flexible activity management, application of digital technologies, and rapid communication. Collectively, these mechanisms contributed to enhanced ethical behavior among students, strengthened the school’s organizational culture, reduced drug-related problems within the community, and fostered exemplary youth role models.